Obesity and disease severity magnify disturbed microbiome-immune interactions in asthma patients - David Michalovich (Nature Portfolio, 2019)
Here, the authors characterize immunological and microbiome alterations in a cohort of obese asthmatics, finding that disease severity negatively correlates with fecal abundance of Akkermansia muciniphila, and show in a mouse model that administration of A. muciniphila reduces airway hyper-reactivity and airway inflammation.